2015
DOI: 10.1007/s00395-015-0464-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of no-reflow and reperfusion injury with the synthetic 17β-aminoestrogen compound Prolame is associated with PI3K/Akt/eNOS signaling cascade

Abstract: A high proportion of primary percutaneous coronary interventions performed in the setting of acute myocardial infarction, concur with inadequate myocardial perfusion at the microvascular level. This phenomenon, known as "no-reflow" contributes to reperfusion injury, poor prognosis and to unfavorable clinical outcome. In this study, we evaluated the hypothesis that the synthetic 17β-aminoestrogen Prolame, may confer cardioprotection and prevent against no-reflow. In an open-chest model of 30-min ischemia and 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 48 publications
0
29
0
1
Order By: Relevance
“…In MSCs, Bcl-2 has been engineered to activate survival pathways capable of suppressing hypoxia-induced apoptosis [125], VEGF and Ang1 for the promotion and formation of new blood vessels [126], survivin to increase cellular survival after introduction into the damaged tissue [127] and the stem cell homing factor SDF-1 [128]. In CPCs, genetic modified targets include nuclear AKT [129], PIM-1 [130–132], ILK [133], nucleostemin [134], notch [135] and beta-adrenergic tolerance through 6-betaARKct [136]. PIM-1, a pro-survival and proliferation gene kinase, has been used to enhance CPCs with demonstrated long-term engraftment, increased cardiac function and reduced fibrotic scar as compared to regular CPCs or placebo in both small [130] and large animal models [132].…”
Section: Current Status Of Adult Stem Cell Therapiesmentioning
confidence: 99%
“…In MSCs, Bcl-2 has been engineered to activate survival pathways capable of suppressing hypoxia-induced apoptosis [125], VEGF and Ang1 for the promotion and formation of new blood vessels [126], survivin to increase cellular survival after introduction into the damaged tissue [127] and the stem cell homing factor SDF-1 [128]. In CPCs, genetic modified targets include nuclear AKT [129], PIM-1 [130–132], ILK [133], nucleostemin [134], notch [135] and beta-adrenergic tolerance through 6-betaARKct [136]. PIM-1, a pro-survival and proliferation gene kinase, has been used to enhance CPCs with demonstrated long-term engraftment, increased cardiac function and reduced fibrotic scar as compared to regular CPCs or placebo in both small [130] and large animal models [132].…”
Section: Current Status Of Adult Stem Cell Therapiesmentioning
confidence: 99%
“…Studies have shown that the PI3K/ Akt pathway reduces I/R injury upon its activation via opening of the mitoK ATP channel, where it radiates key effectors of the mitochondrial apoptosis pathway, including Bcl-2, Bax, and glycogen synthase kinase-3beta, and ultimately reduces the I/R injury [4,18,24]. Additionally, NO has been shown to induce the activation of PI3K/Akt signaling pathway [13] and many studies have demonstrated its protective effects following I/R injury in animal models [11,34]. However, the precise mechanisms underlying the protective effects of nicorandil against I/R injury during DHLF are not well understood.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Gent and colleagues showed that mice given lifetime ivabradine treatment had a significantly longer lifespan than untreated mice, though they could not determine whether the longevity was secondary to heart rate reduction or to potential pleiotropic effects of ivabradine 43. The authors hypothesized that reduced reactive oxygen species formation, either because of heart rate reduction or a direct action of ivabradine, would be mechanistically consistent with greater longevity, particularly as mice die mostly from cancer and not from cardiovascular disease, where the benefit from heart rate reduction would be more direct.…”
Section: Discussionmentioning
confidence: 99%